Complications and Clinical Manifestations of Febrile Urinary TractInfections in Children — A Case-Control Study (The Planet, 2024)
Introduction: Urinary tract infections (UTIs) are one of the most common infections in children, particularly in those presenting with fever. Febrile UTIs, if left untreated or poorly managed, can lead to significant morbidity, including kidney damage. This study aims to investigate the clinical manifestations and complications of febrile UTIs in children aged 5–12 years. Methods & Materials: This case-control study was conducted at the Department of Paediatrics, Comilla Medical College Hospital, Comilla, from January 2013 to July 2013. A total of 50 cases and 50 suitably matched controls were enrolled by systematic random sampling technique. Data were processed and analyzed using computer software and SPSS. Result: This study found that febrile urinary tract infections (UTIs) in children were characterized with fever present in 100% of cases, abdominal pain in 90%, and frequency of micturition in 72%. Urine analysis revealed abnormal results (PUS cells >5) in all 50 cases (100%), while bacterial growth was found in 23 (46%) cases. Imaging studies identified structural abnormalities in 8 (16%) of the cases. The study also reported a variety of complications, including dysuria in 30 (60%), poor feeding in 35 (70%), irritability in 9 (18%), and tenderness in the renal angle (36%) and suprapubic region (38%). Conclusion: Fever and abdominal pain were the most common symptoms, with dysuria, frequent urination, and poor feeding also reported. Urine tests confirmed infection, and imaging revealed structural abnormalities in some cases. Early diagnosis with clinical evaluation, urine tests, and imaging is crucial to prevent renal damage.
Keywords: Urinary tract infection; Complications; Clinical manifestations; Urine R/E; Ultrasound